ADVOKASI KELOMPOK KEPENTINGAN DAN PENATAAN RUANG:PAGUYUBAN PEDAGANG KAKI LIMA DI KOTA SEMARANG - Muhammad Zacky Permana; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2026)
This study aims to analyze the advocacy practices carried out by the street vendors’ association (Paguyuban PKL) in the Simpang Lima area of Semarang City within the context of urban spatial regulation. Although the arrangement of street vendors has been formally regulated through local government policies and designated location decrees, empirical findings reveal that the implementation process involves informal interactions between the association and state actors. This research positions advocacy not merely as an articulation of interests, but as a strategy of power exercised within the arena of informal politics. This study employs a qualitative approach using a case study method. Data were collected through in-depth interviews with association leaders and relevant stakeholders, field observations, and document analysis of related policies. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the street vendors’ association mobilizes social capital in the form of networks and informal relations with bureaucratic actors, as well as economic capital derived from their contribution to local economic activities, as instruments in negotiating spatial arrangements. Advocacy practices primarily operate through informal communication, negotiation, and bureaucratic discretion. In this context, advocacy functions as a mechanism for the production and reproduction of power in managing access to urban space. Consequently, public space, which is normatively categorized as a public good, undergoes a transformation toward the characteristics of a club good, where access and control are mediated by the association’s internal structure and power relations.